2011
DOI: 10.1111/j.1600-0838.2009.01080.x
|View full text |Cite
|
Sign up to set email alerts
|

Substance P injections enhance tissue proliferation and regulate sensory nerve ingrowth in rat tendon repair

Abstract: Tendon healing is characterized mostly by slow rehabilitation and, as in tendinopathy, aberrant, protracted sensory nerve ingrowth. This study investigated whether administration of the sensory neuropeptide substance P (SP) could enhance healing and modulate sensory nerve plasticity after Achilles tendon rupture. Fifty-four male Sprague-Dawley rats were allocated to three groups, all receiving six daily injections post-rupture of; (1) SP (10(-6) mol/kg body weight)+endopeptidase inhibitors captopril and thiorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 20 publications
2
43
0
Order By: Relevance
“…70 Furthermore, elevated levels of the glutamate receptor, N-methyl-D-aspartate receptor type 1 (NMDAR1) have also been documented in chronic tendinopathy. 71 In this study of patients with symptomatic patellar tendinopathy there was a 9-fold increase of NMDAR1 and a 10-fold increase of glutamate compared with controls.…”
Section: Matrix Metalloprotinase Activity Inhibition and Regulationmentioning
confidence: 57%
“…70 Furthermore, elevated levels of the glutamate receptor, N-methyl-D-aspartate receptor type 1 (NMDAR1) have also been documented in chronic tendinopathy. 71 In this study of patients with symptomatic patellar tendinopathy there was a 9-fold increase of NMDAR1 and a 10-fold increase of glutamate compared with controls.…”
Section: Matrix Metalloprotinase Activity Inhibition and Regulationmentioning
confidence: 57%
“…Exogenous administration of SP promoted wound and tendon healing. 10,[36][37][38][39] Moreover, inhibition of neutral endopeptidase, which degrades SP, augments epithelialization. 40 Thus, an exogenous SP supply after tendon injury resulted in increased fibroblast number, diameter of the organized collagen, and the amount of collagen III after injury (Fig.…”
mentioning
confidence: 99%
“…A second report, originating from the same laboratory utilizing the same model, showed that treatment with SP also increased stress at maximal load and work to maximal load in healing Achilles tendon, although stiffness was not improved compared to controls, and actual failure loads were not reported (185). An interesting observation from one of these studies was that the SP treated group exhibited an accelerated withdrawal of sensory nerve fibers from the injury site during healing (184). This observation may be interesting in the context of human tendinopathy with protracted, pathological sensory nerve fiber ingrowth in the tendon.…”
Section: Stimulated Neuronal Signallingmentioning
confidence: 92%
“…Local injections of SP combined with the neutral endopeptidases thiorphan and captopril were used as a treatment for Achilles tendon rupture in rats (183,184). This resulted in dose dependent increases in fibroblast number at the injury site between 1 and 6 weeks after injury.…”
Section: Stimulated Neuronal Signallingmentioning
confidence: 99%
See 1 more Smart Citation